Board meeting frequency and financial performance: a case of listed firms in vietnam - Hanh, Le Thi My; Irene, Wei Kiong Ting; Kweh, Qian Long; Hoanh, Lam Thi Hoang (UNIMAS, 2018)
This study investigates the effect of board meeting frequency on the financial performance of listed firms in a fiscal year. We use 94 firms listed on Ho Chi Minh Stock Exchange from 2013 to 2015. Financial performance is measured as returns on asset, equity and sales. Results show that board meeting frequency exerts a negative effect on the financial performance of the sample firms. High board meeting frequency equates to low returns on asset, equity and sales. Overall, the quality of board meetings is an important factor that contributes to financial performance.